An Ecore based Petri net type definition for PNML IOPT models - Ribeiro, J. (2013)
In this paper we present a new Input-Output Place-Transition (IOPT) Petri net metamodel and its Petri Net Type Definition (PNTD) using a RELAX NG grammar. This new version introduces changes to the previous metamodel to ensure that the model representation follows the International Standard guidelines to extend PNML and to fully support automatic generation of models state space. The validation of this revised metamodel and the corresponding PNTD were made through case studies. The new concepts introduced in the metamodel have demonstrated their validity and usefulness, in the automatic generation of executable code and the state space. The correctness of the RELAX NG grammar was also validated through case studies.